Effect of Delay In Starting Adequate Treatment On Recovery Time Of Head And Neck Space Infections - Hasan, Sajid; Khan, Saeed Hossain; Arefin, Raihan Ul; Kamruzzaman, Mohammad (Update Dental College Journal, 2018)
Aim: This prospective observational study was conducted to find out “delay of starting adequate treat- ment” as a prognosis predictor of head and neck space infections. Material and method:50 patients were selected purposively with inclusion criteria of presence of head and neck space infections. The exclusion criteria was presence of any other co-morbid diseases. After proper evaluation and diagnosis, adequate treatment was provided. Structured questioner method was used to collect data related to delay of starting of treatment and outcome of disease. Result: In this prospective observational study, caries was the most frequent cause of space infection. Time elapsed in between starting of symptoms and initiation of adequate treatment (timing of starting treatment) was 8.52(±6.689) days. This delay of starting treatment causing increased recovery time significantly (P= < 0.001 level). However, there was no correlation in between delay of starting treat- ment and number of involved space infection but later has impact on recovery time. Conclusion: Information about delay of starting treatment and number of involved spaces can be used as a prognosis predictor in HNSI. Update Dent. Coll. j: 2018; 8 (1): 41-44